Tertiary education trust fund intervention on academic staff capacity building in Lagos State University, Nigeria - Abdulaziz Isiaka; Olokooba Issa Nasiru; Iyekolo Olushola (Intelektual Pustaka Media Utama, 2020)
The study adopted the descriptive survey research design to assess Tertiary Education Trust Fund intervention on academic staff capacity building in Lagos State University, Nigeria. The population for this study was all academic staff of Lagos State University. Two purposes of the study were raised and two research questions were also formulated. One hundred and ninety-six questionnaires were randomly administered to one hundred and ninety-six (196) academic staff in the university. The questionnaire titled “Tetfund Intervention on Academic Staff Capacity Building Questionnaire” was used for data collection. The findings of the study revealed that provision of infrastructure for effective teaching and learning is the major the fund intervention towards qualitative transformation of academic staff in Lagos State University. The finding of the study also showed that the fund intervention in Lagos State University for academic staff capacity building was major priority. Based on the findings of the study, it was recommended that the fund should eliminate the level of bureaucratic bottlenecks often associated with accessing approved funds. Having noted that University education is cost-effective, donor agencies and philanthropic individuals and groups, should assist governments in funding tertiary education in the country.